Accuracy of nature of call screening tool in identifying patients requiring treatment for out of hospital cardiac arrest. Issue 4 (6th February 2019) - Green, Jonathan David; Ewings, Sean; Wortham, Richard; Walsh, Bronagh
Abstract : Background: A new pre-triage screening tool, Nature of Call (NoC), has been introduced into the telephone triage system of UK ambulance services which employ National Health Service Pathways (NHSP). Its function is to provide rapid recognition of patients who may need immediate ambulance dispatch for out-of-hospital cardiac arrest (OHCA) and withholding dispatch for other calls while further triage is undertaken. In this study, we evaluated the accuracy of NoC and NHSP in identifying patients with potentially treatable or imminent OHCA. Methods: This retrospective, observational study reviewed consecutive calls to a UK ambulance service between October 2016 and February 2017 in which NOC, and then NHSP were applied sequentially. Only those calls for which a corresponding electronic Patient Clinical Record was available were included. Sensitivity and specificity of NOC and NHSP for recognition of an OHCA were determined by comparing allocated priority dispositions with an OHCA Treatment Registry (OHCATR). Results: Of 96 423 calls received, 71 373 were reviewed. For 590 (0.8%) of these calls, the patients received treatment for OHCA. NOC identified 458 OHCATR patients; NHSP identified 467; together they identified 496. NoC captured 29 patients not identified by NHSP; NHSP captured 38 patients not identified by NOC. For NOC sensitivity was 77.6% (95% CI 74.1 to 80.8) and specificity 86.9% (95% CI 86.6 to 87.1). NHSP sensitivity was 79.2% (95% CI 75.7 to 82.2) and specificity 93.4% (95% CI 93.2 to 93.6). NoC and NHSP combined had a sensitivity of 84.1% (95% CI 80.9 to 86.8) and specificity of 85.3% (95% CI 85.1 to 85.6). Conclusions: NoC and NHSP call categorisation each achieved similar sensitivity for the identification of OHCATR, identifying most of the same patients, but each captured unique patients. Using both methods sequentially improved accuracy. The 16% of OHCATR patients not identified by either method present a challenge to ambulance dispatch systems.